25.9k views
2 votes
PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!!!

The recursive rule for a geometric sequence is given.

PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!!! The recursive rule for a geometric-example-1
User YoshiMbele
by
5.5k points

1 Answer

2 votes

Answer:
\bold{a_n=2\bigg((1)/(3)\bigg)^(n-1)}

Explanation:


\text{The general form of the recursive rule is:}\ a_n=r\cdot a_(n-1)\\ \text{where r is the common ratio.}\ \text{The recursive rule provided is:}\\ a_n=(1)/(3)a_(n-1)\ \text{so, r} = (1)/(3)}\\\\\text{The general form of the explicit rule is:}\ a_n=a_1(r)^(n-1)\\\text{where}\ a_1\ \text{is the first term and r is the common ratio}.\\\\\text{So, the explicit rule with the information provided is:}\\a_n=2\bigg((1)/(3)\bigg)^(n-1)

User SoluableNonagon
by
5.3k points